Environmental controls of soil fungal abundance and diversity in Australia's diverse ecosystems - Viscarra Rossel, Raphael; Yang, Y.; Bissett, A.; Behrens, T.; Dixon, Kingsley; Nevil, P.; Li, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Soil fungi are vital for ecosystem functioning, but an understanding of their ecology is still growing. A better appreciation of their ecological preferences and the controls on the composition and distribution of fungal communities at macroecological scales is needed. Here, we used one of the most extensive continental-scale datasets on soil fungi and modelled the relative abundance of dominant fungal phyla and community diversity in Australian soils from forests, grasslands, shrublands, woodlands, and croplands. Across these diverse ecosystems, the Ascomycota and Basidiomycota dominate Australian soils, and fungal diversity declines as climates become more arid. Climate and the water balance exert dominant control on soil fungal abundance and diversity, mediated by interactions between ecosystem type, the ensuing vegetation and edaphic factors, such as organic matter, clay and iron-oxide mineralogy, pH and nutrients. Soil organic matter and mineralogy, represented by absorptions of visible–near-infrared (vis–NIR) radiation, helped to improve characterisation of the abiotic controls on soil fungi. This better representation of edaphic factors improved the predictability of the models by up to 40%. Our findings contribute to the understanding of fungal ecology at a macroecological scale. They help to appreciate better the links between fungi, soil and the environment, which underpin ecosystem stability and resilience and have implications for developing strategies for preservation, adaptation and mitigation of global change.